(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the trend of searching for information about dengue fever in Vietnam in the period 2024-2025 by space and time using the Google Trends tool. Subjects and methods: The descriptive study uses secondary data from the Google Trends platform, analyzing Vietnamese keywords related to dengue fever searched by users in Vietnam from August 2024 to July 2025. Data were processed using Excel, analyzed by SVI by month and by locality. Results: The search index increased in November 2024 (SVI: 95), decreased to the lowest level in April 2025 (SVI: 29), then increased again in July 2025. Hai Phong, Dak Nong, and Quang Binh were localities with high search levels. The most popular keywords were “Dengue fever” (100), “having Dengue fever” (93), while keywords related to treatment and testing had lower indexes (18-21). Conclusion: Search trends reflect seasonal and geographical community interest, showing the potential for applying Google Trends as a complementary tool in epidemiological surveillance and public health communication in Vietnam.